Effect of Herbal Galactogogue (Sanjivani biokseera) on Milk Yield and Milk Constituents in Lactating Kankrej Cattle at Organised Farm - Panchasara, HH; Chaudhari, AB; Patel, DA; Gami, YM; Patel, MP (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was conducted to evaluate the effect of feeding herbal galactogogue preparation (Sanjivani biokseera) on the milk yield and  milk constituents in lactating Kankrej cows. Thirty-two lactating Kankrej cows in their 1st to 6th lactation were taken for the experiment  from 3 days after calving up to 52 days postpartum. All the animals were fed as per the standard seasonally available roughages and  concentrates to meet their nutritional requirements. The cows were randomly divided into two uniform groups of 16 cows in each  according to initial milk yield and milk composition. The animals in group-I were not given any supplement and served as control. The  animals in group-II were given Sanjivani biokseera (Naturewell Industries) @ 60 g per day for 1-month, commencing 3 days after calving,  in addition to the usual feeds/fodders. A clear difference was observed in milk yield from day 8 onward of experiment between groups  with significant (p
Keywords: Herbal galactogogues; Kankrej cows; Milk yield; Milk constituents